STRATEGI PEMASARAN KUE PIA ANYEN DI DESA SEA KECAMATAN PINELENG - Vika Singgita Findia Dien; Lyndon Reinhard Jacob Pangemanan; Celcius ., Talumingan (AGRI-SOSIOEKONOMI, 2019)
This study aims to look at the marketing strategy of "Anyen" pia cake in the sea village of Pineleng District. This research was conducted for 3 months, starting from March to June 2019. The data used in this study are primary data obtained from direct interviews with Anyen pia cake business owner, Mr. Lexy Pelealu and secondary data from 37 respondents of Anyen pia cake customers. fill out a questionnaire calculated on a Likert scale. The results of this study indicate that the marketing strategy for Anyen Pia is in the excellent category. Where aspects of the marketing mix of products 78.61%, aspects of the marketing mix of prices 85.97%, aspects of the marketing mix of places 81.07%, and aspects of the marketing mix of promotion of 85.97%.*eprm*